Current Trends and Future Prospects in Controlling the Citrus Nematode: Tylenchulus semipenetrans - Anil Baniya; Omar Zayed; Jiranun Ardpairin; Danelle Seymour; Adler R. Dillman (Agronomy, 2025)
Citrus nematode (Tylenchulus semipenetrans) is one of the dominant plant-parasitic nematodes in citrus-growing regions, resulting in an average yield loss between 10 and 30%. Tylenchulus semipenetrans is a sedentary semi-endoparasitic nematode that infects the roots of citrus trees, causing stunted growth, reduced fruit yield, and poor fruit quality; collectively this pathology and thus the disease caused is referred to as the slow decline of citrus. Despite its huge importance, the citrus nematode is regarded as a neglected parasite, and most research focuses on biological control and integrated pest management. Advancements in understanding the molecular mechanisms of other plant-parasitic nematodes, such as sedentary endoparasites with biological similarities to citrus nematodes, can be leveraged to gain deeper insights into the molecular mechanisms of citrus nematodes. In this review, we examine the biology, and integrated pest management of citrus nematodes, and explore future research directions toward understanding the role of genomics, gene-editing tools, and the molecular mechanisms of host-seeking and effectors used by other plant-parasitic nematodes to cause infection, which can serve as a foundation for future work in citrus nematode management.